1995
DOI: 10.1007/bf01262323
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the p53 protein in malignant melanomas as a prognostic indicator

Abstract: It is currently widely accepted that the tumour suppressor gene p53 is critically involved in the proliferation and differentiation of tumour cells including melanoma cells. In the present study, we examined 60 cases of primary melanoma to compare the expression of p53 protein with conventional prognostic markers for melanoma such as clinical and histological parameters. No correlation was found between the p53 protein and clinical factors except for the presence of a metastatic node and development to clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
2
6

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 26 publications
4
23
2
6
Order By: Relevance
“…Early studies indicated an increased expression of p53 protein in almost 100% of the tumors (Stretch et al, 1991;Akslen and Mørkve, 1992;Weiss et al, 1993Weiss et al, , 1995McGregor et al, 1993), but others found a lower proportion, of 5-50% (Yamamoto et al, 1995;Lassam et al, 1993;Cristofolini et al, 1993;Flørenes et al, 1994). In the present study, marked differences in immunostaining were found using various p53 antibodies.…”
Section: Discussioncontrasting
confidence: 29%
See 1 more Smart Citation
“…Early studies indicated an increased expression of p53 protein in almost 100% of the tumors (Stretch et al, 1991;Akslen and Mørkve, 1992;Weiss et al, 1993Weiss et al, , 1995McGregor et al, 1993), but others found a lower proportion, of 5-50% (Yamamoto et al, 1995;Lassam et al, 1993;Cristofolini et al, 1993;Flørenes et al, 1994). In the present study, marked differences in immunostaining were found using various p53 antibodies.…”
Section: Discussioncontrasting
confidence: 29%
“…In cutaneous melanoma, p53 changes have been repeatedly reported. Some early studies have indicated that p53 protein expression was increased in a high proportion of primary melanomas, up to nearly 100% (Stretch et al, 1991;Akslen and Mørkve, 1992;Weiss et al, 1993Weiss et al, , 1995McGregor et al, 1993), whereas others found a lower frequency (about 5-50%) of p53 tumor positivity by immunohistochemistry (Yamamoto et al, 1995;Lassam et al, 1993;Cristofolini et al, 1993;Flørenes et al, 1994). Alterations of the p53 gene have been described in about 20-25% of metastatic cutaneous melanomas (Flørenes et al, 1994;Sparrow et al, 1995;Hartmann et al, 1996).…”
Section: Wiley-liss Incmentioning
confidence: 99%
“…However, within the subgroup of patients with thick (>1.5 mm) tumours, already known to have an impaired survival, p53 index independently separated those patients into different prognostic groups. Most studies to date have shown either no correlation (Sparrow et al, 1995;Weiss et al, 1995;Talve et al, 1996) or, like our study, an inverse (Yamamoto et al, 1995;Vogt et al, 1997) correlation between the p53 expression and outcome of human cutaneous malignant melanoma.…”
Section: Discussionmentioning
confidence: 78%
“…This is often in the absence of point mutations in the gene (McGregor et al, 1993;Albino et al, 1994;Sparrow et al, 1995) but is associated with tran scriptional inactivity (Houben et al, 2011). Moreover, corre lation of p53 immunoreactivity with advanced melanoma and unfavorable prognosis has been demonstrated (McGregor et al, 1993;Yamamoto et al, 1995). Small molecular weight variants of p53 have also been demonstrated in melanoma and, in some instances, are expressed at higher levels than fulllength WTp53 (AveryKiejda et al, 2008).…”
mentioning
confidence: 98%
“…High levels of p53 expression in melanoma cells and tissue samples have been reported in numerous studies (Bártek et al, 1991;Stretch et al, 1991;Akslen and Mørkve, 1992;McGregor et al, 1993;Yamamoto et al, 1995;Hussein et al, 2003;Houben et al, 2011;Knopf et al, 2011). This is often in the absence of point mutations in the gene (McGregor et al, 1993;Albino et al, 1994;Sparrow et al, 1995) but is associated with tran scriptional inactivity (Houben et al, 2011).…”
mentioning
confidence: 98%